Mitigating Algorithmic Bias Through Probability Calibration: A Case Study on Lead Generation Data - Miroslav Nikolić; Danilo Nikolić; Miroslav Stefanović; Sara Koprivica; Darko Stefanović (Mathematics, 2025)
Probability calibration is commonly utilized to enhance the reliability and interpretability of probabilistic classifiers, yet its potential for reducing algorithmic bias remains under-explored. In this study, the role of probability calibration techniques in mitigating bias associated with sensitive attributes, specifically country of origin, within binary classification models is investigated. Using a real-world lead-generation 2853 × 8 matrix dataset characterized by substantial class imbalance, with the positive class representing 1.4% of observations, several binary classification models were evaluated and the best-performing model was selected as the baseline for further analysis. The evaluated models included Binary Logistic Regression with polynomial degrees of 1, 2, 3, and 4, Random Forest, and XGBoost classification algorithms. Three widely used calibration methods, Platt scaling, isotonic regression, and temperature scaling, were then used to assess their impact on both probabilistic accuracy and fairness metrics of the best-performing model. The findings suggest that post hoc calibration can effectively reduce the influence of sensitive features on predictions by improving fairness without compromising overall classification performance. This study demonstrates the practical value of incorporating calibration as a straightforward and effective fairness intervention within machine learning workflows.